Knowledge Map : Current Projects and Practices - World Bank (Washington, DC, 2012)
Locating and identifying the uses of information and communication technologies (ICTs) to benefit education in developing countries is a tedious, difficult, time-consuming, and ad hoc task. No standard reference or methodology exists for identifying such investments. Observations and conclusions on how ICTs are actually used in schools are drawn almost exclusively from Organization for Economic Co-operation and Development (OECD) experience. Little such data exists for least development countries LDCs, and essentially none for countries most at risk of meeting education-related Millennium Development Goals (MDGs). Emerging evidence from OECD countries suggests that even massive investments in ICTs in schools may not bring about the desired changes in teaching and learning processes unless such investments are supported by similar initiatives to improve access to ICTs outside of the school environment. This may be especially important for uses of ICTs to support education for all (EFA) goals, as effective use in school may require high levels of access outside school if gains in such investments are to be maximized, especially where ICTs are to be used for communication purposes.